PREVALENCE OF SYPHILIS AND HIV INFECTION IN BLOOD DONORS IN COSMOPOLITAN LAHORE DURING THE YEAR 2014 - Hamid Mahmood; Umer Saeed Ansari; Mohammad Aslam (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: To identify the reasons for increase in number of patients suffering from syphilis, among the blood donors reporting in Lahore. SELECTED BLOOD BANKS: Chughtai Medical Laboratories, Gulberg. Doctors Hospital, Johar town. National Hospital, DHA, Lahore. SAMPLE SIZE: samples were collected from 23,156 donors. STUDY DURATION: st st From 1 January, 2014 to 31 December 2014. METHODS: Large numbers of blood donors were screened for treponema antibodies in the serum. ARCHITECT SYPHILIS TP TEST is a chemiluminescent micro particle immunoassay (CMIA) for the qualitative detection of antibody to Treponema pallidum (TP) in human serum. RESULTS: Out of 23,156 blood donors screened, 1124 donors (4.9%) were detected positive for syphilis. One donor was HIV positive (0.0043%). Among the infected donors, 29.92% cases were O +ve, while only 1.18% cases were AB-ve blood groups. HIV positive individual was B+ve blood group. CONCLUSION: The number of syphilis patients is on the rise in Lahore due to Treponerma Pallidum, which is evident from screening of large number of blood donors in high-turnout blood banks in Lahore. Moreover, public awareness campaign is required to educate the citizens regarding the complications and spread of this disease